The Relationship Between The Length of Time Undergoing Hemodialysis and The Fulfillment of Sexual Needs in Male Patients with Chronic Kidney Failure in The Malahayati Hemodialysis Room of dr. Saiful Anwar Hospital, Malang - Sri Masriah; Achmad Dafir Firdaus; Andi Surya Kurniawan (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Male patients undergoing prolonged hemodialysis can experience a decrease in reproductive system function, leading to sexual dysfunction. The aim of the research was to determine the relationship between the length of time undergoing hemodialysis and the fulfillment of sexual needs in chronic kidney failure patients in the Malahayati Room of dr. Saiful Anwar Hospital, Malang. The research design uses non-experimental correlational research with a cross-sectional approach. The population of this study were all male chronic kidney failure sufferers who underwent hemodialysis in the Malahayati Hemodialysis Room of dr. Saiful Anwar Hospital, Malang. As of June 2023, there were 71 people. The samples in this study were all male CKD patients of productive age (15–64) taken using the purposeful sampling method. Data collection uses a questionnaire. The results of the study showed that almost half of the respondents with CKD underwent hemodialysis in the Malahayati Room of dr. Saiful Anwar Hospital, Malang for > 24 months, namely 41.80%, and as many as 50.90% of respondents who underwent hemodialysis had their sexual needs still fulfilled. The results of Chi Square test showed there was a relationship between the length of time undergoing hemodialysis and the fulfillment of sexual needs in male CKD patients in the Malahayati Room of dr. Saiful Anwar Hospital, Malang (p value 0,00). It is hoped that hospitals can provide services that support the understanding of CKD sufferers, such as providing appropriate health education to patients so that they understand the changes that will occur in their health.